Evaluation of corrective actions of feedback from clinicians on Clinical Laboratory Services at Bamenda Regional Hospital Laboratory, Cameroon - Victor N. Fondoh; Charles N. Awasom; Rebecca Enow-Tanjong; Richard M. Fondoh; Patrick Njukeng; Judith Shang; Juliana Ndasi; Moses Samje; Claris N. Muluh; Thompson N. Kinge (African Journal of Laboratory Medicine, 2020)
Background: Customers’ satisfaction is imperative for success. Clinical laboratories continuously strive to attain very high levels of customer satisfaction to serve their clients and maintain accreditation. The concept of customer satisfaction has not yet been asserted in most clinical laboratories in Cameroon.